Improving the Students’ Listening Comprehension through Aural-Oral Language Approach - Sujariati Sujariati (Linguistic, English Education and Art (LEEA) Journal, 2020)
This research aimed to know the effectiveness of using Aural-oral approach to improve the students’ listening comprehension, and to know the students’ activeness toward teaching learning process through Aural-oral approach at the eleventh grade students of SMAN 1 Makassar. Two cycles had been conducted, where each cycle consisted of four meetings. It implemented Aural-oral approach as an approach to improve the students’ listening comprehension and employed listening test as instrument. A number of subjects of the research were 16 students. It is consist of 9 women and 7 men. The researcher took real data from the school to know the students’ listening comprehension. The students’ mean score of listening achievement at D-Test was 50.69, at the cycle I was 65.28 and at the cycle II was 75.93. The result of the student's listening test in cycle II had improved in significant score, where the means score of students in distinguish phonemes was 87.5, in understanding Statement was 50, and in understanding dialogue was 90.28. It means that the students’ mean score at the cycle II was 75.93 reached the target score 75 and the students’ activeness toward teaching learning process by using Aural-oral approach was improved. It can be seen from the observation result of the students’ activeness in the classroom from the first meeting at the first cycle until at the last meeting in cycle II always grow up. It could be stated that the research was successful. Keyword: Listening Comprehension, Aural-oral Approach, Student’ Listening, Student’s Activeness